An eQTL variant of ZXDC is associated with IFN-γ production following Mycobacterium tuberculosis antigen-specific stimulation. Issue 1 (December 2017) - Jabot-Hanin, Fabienne; Cobat, Aurélie; Feinberg, Jacqueline; Orlova, Marianna; Niay, Jonathan; Deswarte, Caroline; Poirier, Christine; Theodorou, Ioannis; Bustamante, Jacinta; Boisson-Dupuis, Stéphanie; Casanova, Jean-Laurent; Alcaïs, Alexandre; et al.
Abstract There is a large inter-individual variability in the response toMycobacterium tuberculosis infection. In previous linkage analyses, we identified a major locus on chromosome region 8q controlling IFN-γ production after stimulation with live BCG (Bacillus Calmette-Guérin), and a second locus on chromosome region 3q affecting IFN-γ production triggered by the 6-kDa early secretory antigen target (ESAT-6), taking into account the IFN-γ production induced by BCG (IFNγ-ESAT6BCG ). High-density genotyping and imputation identified ~100, 000 variants within each linkage region, which we tested for association with the corresponding IFN-γ phenotype in families from a tuberculosis household contact study in France. Significant associations were replicated in a South African familial sample. The most convincing association observed was that between the IFNγ-ESAT6BCG phenotype and rs9828868 on chromosome 3q (p  = 9.8 × 10−6 in the French sample). This variant made a significant contribution to the linkage signal (p  < 0.001), and a trend towards the same association was observed in the South African sample. This variant was reported to be an eQTL of theZXDC gene, biologically linked to monocyte IL-12 production through CCL2/MCP1. The identification of rs9828868 as a genetic driver of IFNγ production in response to mycobacterial antigens provides new insights into human anti-tuberculosis immunity.